KOMBINASI LARVA LALAT BUNGA (Hermetia illucens L.) DAN PELET UNTUK PAKAN IKAN PATIN JAMBAL (Pangasius djambal) - Soikar Hariadi; Chandra Irsan; Marini Wijayanti (Universitas Sriwijaya, 2014)
ABSTRACT The objective of study was to know the effect of combination of black soldier fly larva and pellet for growth and survival rate of Pangasius djambal and also to know the optimal food proportion combination of black soldier fly larva and pellet for growth and survival rate of P. djambal. The experiment was arranged has been done for 56 days in the Jambi Freshwater Aquaculture Development Center (JFADC). Fish that used were P. djambal with average weight of 10.17 g. They were placed in aquarium size 100x50x40 cm3 with the density 10 fish/aquarium. The experiment was arranged in a completly randomized design (CRD) with five treatments. Food combination tested were as follows : P1 (100% pellet), P2 (75% pellet and 25% black soldier fly larva), P3 (50% pellet and 50% black soldier fly larva), P4 (25% pellet and 75% black soldier fly larva), P5 (100% black soldier fly larva). The measured parameters were daily growth rate, food convertion ratio, protein efficiency ratio and survival rate of P. djambal. The result of this current experiment indicated that combination of black soldier fly and pellet influenced daily growth rate, food convertion ratio, protein efficiency ratio, but not influenced survival rate of P, djambal. The optimal food combination proportion wich gave the best daily growth rate, food convertion ratio, protein efficiency ratio was 97.0-82.5% pellet and 17.5-21.0% black soldier fly larva. The survival rate of P. djambal for all treatment was 100%. Keywords: Pangasius djambal, growth, survival rate, black soldier fly larva, feed